"I Am Here to Assist You Today": The Role of Entity, Interactivity and Experiential Perceptions in Chatbot Persuasion. Issue 4 (1st October 2020) - Ischen, Carolin; Araujo, Theo; van Noort, Guda; Voorveld, Hilde; Smit, Edith
ABSTRACT: Online users are increasingly exposed to chatbots as one form of AI-enabled media technologies, employed for persuasive purposes, e.g., making product/service recommendations. However, the persuasive potential of chatbots has not yet been fully explored. Using an online experiment ( N = 242), we investigate the extent to which communicating with a stand-alone chatbot influences affective and behavioral responses compared to interactive Web sites. Several underlying mechanisms are studied, showing that enjoyment is the key mechanism explaining the positive effect of chatbots (vs. Web sites) on recommendation adherence and attitudes. Contrary to expectations, perceived anthropomorphism seems not to be particularly relevant in this comparison.